Pelecehan Seksual di Lingkungan Pendidikan Tinggi dalam Perspektif Maqashid al-Syariah - Setyaningrum , Fatimah Khosiyyah; Waty, Wan Hamidah Febry; Salsabilah, Deswita Putri; Habil, Habil; Ardita, Tiara; Fauzan, Ahmad (Journal of Sharia and Legal Science, 2026)
Sexual harassment in higher education is a serious problem that impacts the psychological, academic, and social well-being of students. This phenomenon occurs not only in physical forms, but also verbally and digitally, which is increasingly growing with the use of social media and communication technology. This study aims to analyze the phenomenon of sexual harassment in higher education and examine its impact and prevention efforts from the perspective of Maqashid al-Syariah. This study uses a descriptive qualitative method with a library research approach. Data were obtained from various sources such as scientific journals, books, laws and regulations, and reports from related institutions, which were analyzed descriptively and analytically. The results show that sexual harassment in higher education is influenced by power relations, a culture of seniority, a low understanding of consent, and weak institutional protection systems. Victims of sexual harassment experience multidimensional impacts such as psychological trauma, decreased academic quality, and obstacles in social interaction. From the perspective of Maqashid al-Shariah, sexual harassment violates the principles of protecting honor (ḥifẓ al-‘ird), the soul (ḥifẓ al-nafs), the mind (ḥifẓ al-‘aql), and the lineage (ḥifẓ al-nasl). Therefore, comprehensive prevention and response efforts are needed through strengthening education, a victim-friendly reporting system, and strengthening campus policies to create a safe and dignified educational environment.